Case Report: Adrenocortical carcinoma in children—symptoms, diagnosis, and treatment - Zagojska, Estera; Malka, Magdalena; Gorecka, Adrianna; Ben-Skowronek, Iwona (Frontiers in Endocrinology, 2023)
Adrenocortical carcinomas are extremely rare in the paediatric population. Most of them are hormone-secretive lesions, so they should be taken into consideration in a child with signs of precocious puberty and/or Cushing's syndrome symptoms. Nonetheless, differentiation from benign adrenal tumours is necessary. We report a rare case of adrenocortical carcinoma in a girl and a literature review using PubMed database. A four-year-old girl presented with rapidly progressing precocious puberty and signs of Cushing's syndrome. Imaging of the abdomen revealed a large heterogeneous solid mass. Histopathologic evaluation confirmed adrenocortical carcinoma with high mitotic activity, atypical mitoses, pleomorphism, necrosis and vascular invasion. After tumorectomy a decrease of previously elevated hormonal blood parameters was observed. Genetic tests confirmed Li Fraumeni syndrome. Adrenocortical carcinoma should be suspected in children with premature pubarche and signs of Cushing's syndrome. Diagnosis must be based on clinical presentation, hormonal tests, imaging and histopathological evaluation. Complete surgical resection of the tumour is the gold standard. Oncological treatment in children is not yet well-determined and should be individually considered, especially in advanced, inoperable carcinomas with metastases. Genetic investigations are useful for determining the prognosis in patients and their siblings.